A Study on Histopathological Pattern of Ovarian Tumours in Chittagong Medical College Hospital - Begum, Mahmuda; Rahman, Md Mukhlesur; Jahan, Mahmuda; Rahman, Zillur; Chowdhury, Shahanara (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2020)
Background: Ovarian tumours may either be asymptomatic, found on the routine ultrasound examination or symptoms may be vague till the patient has an acute emergency like torsion or rupture of a benign cyst. The worst is late presentation of malignant ovarian tumour. There is marked variation in the presentation of the tumour as well as in histological types. This study was under taken to analyse modes of presentation and various histopathological patterns of ovarian tumour. Materials and Methods: A total of 69 cases were selected consecutively. The age range was 13-70 years. This study was carried out in the Department of Pathology, Chittagong Medical College and Department of Gynaecology and obstetrics, Chittagong Medical College Hospital during the period from July 2013 to June 2014. The specimens of ovarian tumours were subjected to histopathological examination in the histopathology section. Results : Out of 69 cases, 54(78.3%) were benign and 15(21.7%) were malignant tumour. There was no borderline malignancy in our study. The commonest histological pattern in this study was surface epithelial tumour 49(70.6%) including both benign and malignant tumour followed by germ cell tumour 6(8.7%). The commonest benign tumour was serous cyst cyst adenoma 23(33.4) and malignant tumour was serous cyst adenocarcinoma 5(7.2%). Conclusion : Surface epithelial tumours are the commonest variety of ovarian tumour followed by germ cell tumour. The histological type of ovarian tumour correlates with the prognosis of the tumour. Chatt Maa Shi Hosp Med Coll J; Vol.19 (2); July 2020; Page 13-17